Generalized integral theorems for the quaternionic G-monogenic mappings - Kuzmenko, T.S.; Shpakivskyi, V.S. (Український математичний вісник, 2016)
For G-monogenic mappings taking values in the algebra of complex quaternions, we generalize some analogues of classical integral theorems of the holomorphic function theory of complex variable (the surface and curvilinear Cauchy integral theorems).